Misapplication of Conventional Economic Analysis to Climate Change From the Post-normal Science Perspective: The “Social Cost of Carbon” Myth - Mayumi, Kozo; Renner, Ansel (Frontiers in Climate, 2022)
A critical reflection over the latest comprehensive reporting efforts of the Intergovernmental Panel on Climate Change (IPCC) suggests that applications of cost-benefit analysis (CBA) to climate change, acts which importantly include the monetary calculation of the social cost of carbon (SCC), do not bring about the avoidance or mitigation of pervasive and irreversible climate change issues, issues which could likely continue on a multi-century to millennial time scale. This paper presents, first, a consideration of the most recent IPCC reports that indicated various contemporary problems and threats both to socioeconomic systems and ecosystems on this planet if and when CBA is uncritically applied to climate change issues. Following, a critical reexamination of three crucial concepts, namely, scarcity, discounting and substitution, is made in view of the roles they play in the theoretical foundation of conventional economics. Climate change is shown to be far beyond the scope of these concepts, hence far beyond the scope of CBA and the SCC approach. A discussion of a general alternative approach to addressing climate change issues is presented—one grounded in post-normal science that acknowledges the critical role deep uncertainty plays in many aspects of climate change issues. Reflecting on the need for such an approach and the shortcomings of past, conventional approaches suggest that establishing a process of social resolution of fundamental problems, including participation and mutual learning among relevant stakeholders, rather than a definite solution or technological implementation, is absolutely necessary. A critical study on many aspects of uncertainty is required for reaching constructive disagreement among stakeholders.